PEMANFAATAN NIRA AREN (Arenga pinnata Merr) SEBAGAI BAHAN PEMBUATAN GULA PUTIH KRISTAL - . Baharuddin; Musrizal Muin; Herniaty Bandaso (Forestry Faculty of Universitas Hasanuddin, 2007)
A research was conducted to evaluate the quality of white refined sugar produced from palm tree (Arenga pinnata) using direct and indirect cooking processes. Visual methods were applied to determine color, shape and texture of produced sugar. The sucrose, ash, and other sugar contents as well as dry weight of produced refined sugar were also analyzed. Results showed that the production process using direct cooking resulted in small granulated, dry, compacted and milky white refined sugar, while that using indirect cooking (four hours storage) produced clay granulated, less compacted, dust shape and browning refined sugar. The sucrose, ash, and other sugar contents found in direct cooking process were 10.27%, 0.016%. and 2.68%, respectively, while those found in indirect cooking process were 11.11%, 0.018%, and 2.78%, respectively. Keywords: Palm tree, Arenga pinnata, nira, white refined sugar